Correlates of Aggression in Men With Methamphetamine Use Disorder: Childhood Trauma and Methamphetamine-Use Characteristics - Liu, Mengqi; Pu, Liujin; Liu, Tieqiao; Zhang, Xiaojie; Shen, Hongxian; Deng, Qijian; Wang, Yingying; Li, Wen; Fu, Xiaoya; Yang, Cheng; Fang, Ting; Potenza, Marc N.; et al. (Frontiers in Psychiatry, 2022)
Background: Aggression is common among individuals with methamphetamine use disorder (MAUD) and constitutes a serious public health issue. The current study aimed to examine associations of methamphetamine-use characteristics and childhood trauma with aggression in men with MAUD. Methods: This cross-sectional study was conducted from December 2017 to August 2018. MAUD patients recruited from a compulsory drug rehabilitation center (n=360) and healthy comparison subjects (n=604) completed a survey that measured aggression and childhood trauma, using the Chinese version of Buss-Perry Aggressive Questionnaire (AQ-CV), and the short form of Childhood Trauma Questionnaire (CTQ-SF), respectively. MAUD patients also provided information on methamphetamine-use characteristics such as the age of MAUD onset, MAUD severity, and co-occurring alcohol use disorder (AUD) and tobacco use disorder (TUD) using standard or self-designed questionnaires. Chi-square tests and t-tests were used to compare childhood trauma and aggression between the MAUD and comparison groups. Multiple linear regressions were conducted to determine correlates of overall aggression and its five sub-scales among the MAUD group. Results: The MAUD group had higher childhood trauma and aggression scores than the comparison group. Within the MAUD group, age of MAUD onset, having severe MAUD, co-occurring AUD, co-occurring TUD, and childhood trauma were associated with overall aggression, with slightly different correlates found for its five sub-scales. Conclusions: Our study shows a high level of childhood trauma and aggression in the MAUD group. Both methamphetamine-use characteristics (age of MAUD onset, severe MAUD, co-occurring AUD/TUD) and childhood trauma were associated with aggression in MAUD. Our findings provide useful information on potential risk factors for aggression and inform future longitudinal research to establish causal relationships between these factors and aggression to guide further prevention and treatment programs.